Attending to Values at Stake When a Child is Dying: A Study of Pediatric Intensive Care Unit Nursing from the Perspectives of Bereaved Parents - Avery, Stephanie (Université d'Ottawa / University of Ottawa, 2019)
Existing literature has identified that health care providers significantly shape the experiences of parents at the end-of-life in the pediatric intensive care unit. However, there is a gap in the literature of the specific nursing influence on parental experiences of a child’s death in this context. Employing the interpretive descriptive methodology, this qualitative study was designed to explore parents’ moral experiences of nursing care at the end-of-life in the pediatric intensive care unit, and was analyzed through a lens of nursing ethics. Face-to-face, semi-structured interviews were conducted with eleven parents (six mothers and five fathers) of six children who died in a pediatric intensive care unit at a university-affiliated tertiary hospital in Eastern Canada. Study results revealed close connections between parents’ abilities to meaningfully parent a child through their death and the nursing care that they received at the end-of-life, and highlighted the varying helpful guiding roles that nurses adopted at different moments in parental experiences. Results also indicated that parents attributed immense value to feeling that nurses cared-for-and-about their child and the parents themselves, since this made parents feel that their child’s death mattered to the nurses whom they had formed relationships with. This study enhances our understanding of the individualized nature of parents’ moral experiences of nursing care at the end-of-life in the pediatric intensive care unit, and study results suggest implications for nursing practice, education, and research.
Keywords: Pediatric intensive care; Child's death